Biochemical and microbial changes reveal how aerobic pre-treatment impacts anaerobic biodegradability of food waste - Fisgativa, Henry (Waste management (New York, N.Y.), 2018)
Copyright © 2018 Elsevier Ltd. All rights reserved.